2021 IEEE International Conference on Image Processing (ICIP) 2021
DOI: 10.1109/icip42928.2021.9506082
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Based Analysis of the Impact of Familiarity in the Perception of Deepfake Videos

Abstract: We investigate the brain's subliminal response to fake portrait videos using electroencephalography, with a special emphasis on the viewer's familiarity with the depicted individuals.Deepfake videos are increasingly becoming popular but, while they are entertaining, they can also pose a threat to society. These face-swapped videos merge physiognomy and behaviour of two different individuals, both strong cues used for recognizing a person. We show that this mismatch elicits different brain responses depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The ultimate test might be whether real and AI‐generated faces elicit similar neural responses, given human expertise in face perception (Haxby et al, 2000). So far, research has shown that face‐swap deepfakes elicit similar neural responses to real videos, unless we know one of the people being portrayed (Tauscher et al, 2021). Another study revealed that while neural responses were largely similar, consciously undetectable fake faces can still elicit slightly different neural responses compared with photos (Moshel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate test might be whether real and AI‐generated faces elicit similar neural responses, given human expertise in face perception (Haxby et al, 2000). So far, research has shown that face‐swap deepfakes elicit similar neural responses to real videos, unless we know one of the people being portrayed (Tauscher et al, 2021). Another study revealed that while neural responses were largely similar, consciously undetectable fake faces can still elicit slightly different neural responses compared with photos (Moshel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies on electroencephalographic (EEG) correlates investigated viewers’ ability to distinguish familiar and unfamiliar people from their face-swapped counterparts. Results showed that it is possible to discriminate fake videos from genuine ones when at least one face-swapped actor is known to the observer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that it is possible to discriminate fake videos from genuine ones when at least one face-swapped actor is known to the observer. [7] Investigation of brain reactions to facial expressions is becoming a widespread research area, which aims at better understanding emotional processing and cognitive mechanisms. Even though traditional models suggest that facial identity and expression are processed in distinctive brain areas, the current findings highlight that emotion processing can have a strong influence on facial recognition and memory mechanisms [8].…”
Section: Introductionmentioning
confidence: 99%